Videography supported adhesion, and proliferation behavior of MG‐63 osteoblastic cells on 2.5D titania nanotube matrices. Issue 4 (28th December 2015) - Manurung, Robeth Viktoria; Fu, Pei‐Wen; Chu, Yeh‐Shiu; Lo, Chun‐Min; Chattopadhyay, Surojit
Abstract: Human osteosarcoma cells MG‐63 were cultured on anodically etched titania nanotubes (TiO2 NT), with diameters ranging from 40‐100 nm, to study the correlations between cell proliferation and adhesion on the 2.5 dimensional (2.5D) extracellular matrix (ECM). Unlike other reports, mostly based on mouse stem cells, and 2D cell culture, our studies indicate that the 2.5D NT promote higher proliferation and activity, but less 2D adhesion. Proliferation of the MG‐63 cells was significantly higher in the NTs, the best being the 70 nm diameter sample, compared to planar titania (control). This is consistent with previous studies. However, cellular adhesion was stronger on TiO2 NT with increasing diameter, and highest on the control as obtained from shear stress measurement, paxilin imaging, and western blot measurements probing focal adhesion kinase, p130 CAS, and extracellular‐regulated kinase, in addition to cell morphology imaging by fluorescence microscopy. We provide direct videography of cell migration, and cell speed data indicating faster filopodial activity on the TiO2 NT surfaces having lower adhesion. This evidence was not available previously. The NT matrices promote cells with smaller surface area, because of less 2D stretching. In contrast, on comparatively planar 2D‐like surfaces uniaxial stretching of the cell body with strong anchoring of the filopodia, resulted in larger cell surface area, and demonstrated stronger adhesion. The difference in the results, with those previously published, may be generally attributed to, among others, the use of mouse stem cells (human osteosarcoma used here), and unannealed as‐grown TiO2 NTs used previously (annealed ECMs used here). © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 842–852, 2016.